2009
DOI: 10.1111/j.1756-1051.2009.00495.x
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning of genetic variation in the weedy clonal herb Aegopodium podagraria (Apiaceae) in Sweden

Abstract: Although sexual reproduction appears to be rare in many clonal plant species, the majority of clonal species show similar levels of genetic variation to non‐clonal plant species. Aegopodium podagraria is a noxious garden weed and has become a successful invader in many natural habitats. Earlier studies have demonstrated population differentiation in life‐history traits between different A. podagraria populations in Sweden. In this study, we used three methods to assess genetic variation in this species. Using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
1
1
Order By: Relevance
“…The difference in biomass between genetically identical ramets placed in the North and the South demonstrated that there was strong phenotypic plasticity in Aegopodium . In addition, clones originating from the South and from the North differed in biomass production, suggesting genetically based differentiation between populations, which has previously been found among Aegopodium populations [35]. Contrary to our hypothesis, clones from North Sweden grew larger than plants from South Sweden at both experimental garden sites.…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…The difference in biomass between genetically identical ramets placed in the North and the South demonstrated that there was strong phenotypic plasticity in Aegopodium . In addition, clones originating from the South and from the North differed in biomass production, suggesting genetically based differentiation between populations, which has previously been found among Aegopodium populations [35]. Contrary to our hypothesis, clones from North Sweden grew larger than plants from South Sweden at both experimental garden sites.…”
Section: Discussioncontrasting
confidence: 92%
“…Clones consist of several ramets which have the potential to share resources among them [33] . The compound leaves of Aegopodium become more complex when the plant develops from juvenile to an adult stage [35] . The small, white, five-petaled flowers are organized in compound umbels of 280–1400 flowers, and the shoots are up to 1 m tall [36] .…”
Section: Methodsmentioning
confidence: 99%